Thermochemical Formation of Sodium Borohydride from Sodium Tetramethoxyborate - Ibrahim, Ainee; Paskevicius, Mark; Patel, Aneeka; D’Angelo, A.M.; Humphries, Terry D.; Buckley, Craig E. (2024)
Sodium borohydride (NaBH4) can be used as a hydrogen export material, but thermochemical regeneration from NaBO2 is considered too costly to be feasible mainly due to the cost associated with recycling the metal hydride reagents. This study explores an alternative regeneration route of NaBH4 using NaB(OCH3)4 instead of the widely studied NaBO2. In situ synchrotron X-ray diffraction (SXRD) was utilized to detect the formation of NaBH4 from NaB(OCH3)4 or NaBO2 using various metal hydride reducing agents (NaH, MgH2, Mg2FeH6, LiAlH4, NaAlH4, CaNi5Hx, and LaNi5Hx). NaBH4 formation was detected using NaB(OCH3)4 with NaH (265-320 °C), MgH2 (310-440 °C), NaAlH4 (>140 °C), and LiAlH4 (>20 °C). In contrast, regeneration from NaBO2 required higher temperatures, with NaBH4 formation using MgH2 (>430 °C), Mg2FeH6 (>460 °C), NaAlH4 (>140 °C), and LiAlH4 (>110 °C). Notably, the reaction between NaB(OCH3)4 and NaH yields NaOCH3, whereas the reaction between NaB(OCH3)4 and MgH2 yields Mg(OCH3)2, which may offer lower energy recycling of the metal hydrides. This study also underscores the critical role of hydridic hydrogen (H-) in solid-state thermochemical reactions for NaBH4 formation and presents an alternative regeneration route using NaB(OCH3)4 that could offer cost and energy savings.